Mid‐Holocene drying of K'gari lakes (subtropical eastern Australia) necessitates re‐evaluation of the El Niño–Southern Oscillation climate links and future drying risk - John Tibby; Haidee Cadd; Matthew Harris; Jonathan C. Marshall; Jonathan Tyler; Cameron Barr; Francesca McInerney; Patrick Moss; Claire Murphy; Patricia S. Gadd; Geraldine E. Jacobsen; Mathew Raven; et al. (Journal of Quaternary Science, 2025)
The Holocene history of Australia's climate is surprisingly poorly understood. This is, in part, because of the relatively weak forcing of Holocene climate versus that of the late Pleistocene. However, it is commonly suggested that eastern Australia dried during the mid‐ to late‐Holocene and that this was in response to increased activity in the El Niño–Southern Oscillation (ENSO), in particular, the intensification of the El Niño phase of ENSO. While this has been inferred from numerous locations, data from K'gari (a subtropical sand island adjacent to the east coast) was amongst the first used to develop this hypothesis and features heavily in the discussion of ENSO intensification. This study examines published and new data from three ≥4.5 m deep K'gari lakes that demonstrate a strong drying event during the middle Holocene (from 7640 to 5600 cal a BP), followed by a wetter late Holocene climate. This contrasts somewhat with previous arguments about K'gari's history that suggest a late Holocene drying. In turn, this indicates a need to re‐evaluate the notion that ENSO intensification drove late‐Holocene drying in the region. It also indicates that even large, deep lakes on K'gari, which are iconic landmarks with substantial cultural, ecological and economic values, are vulnerable to drying.